(untitled) (Chittagong University Journal of Biological Sciences, 2013)
In the present investigation five cheese samples were collected and their pH and moisture contents were determined which was found to vary from 6.0 to 6.5 and 35.0-40.0% respectively. Major nutritional factors protein (1N NaOH soluble) and fat (chloroform soluble) of the samples were also analyzed and found 57.9 to 100.0 mg/g protein and 15-25% fat. The samples showed higher number of total bacterial count (5.3×104 - 2.9×107cfu/g) than the load of Lactobacilli (1.9x105 cfu/g) and Streptococci (2.1x105cfu/g). All the isolates were grouped into six on the basis of their morphological and cultural features. Six isolates were selected on the basis of their morphological, cultural, physiological and biochemical characteristics. An attempt was made to identify the isolates. They were found to belong to the three genera viz. Bacillus (S1X3, S1X8, S2Y1, and S2Y2), Staphylococcus (S1X7) and Planococcus (S1X11). They were provisionally identified as Bacillus fastidiosus (S1X3); B. sphaericus (S1X8); B. brevis (S2Y1); B. aminovorans (S2Y2); Staphylococcus saprophyticus (S1X7) and Planococcus citreus (S1X11).The selected isolates were screened for their efficacy in terms of curd and cheese production. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13393 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):99-105, 2009